PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI MATERI SISTEM REPRODUKSI TERINTEGRASI KEILMUAN ISLAM UNTUK SISWA KELAS XI MADRASAH ALIYAH - Rakhmatullah Rakhmatullah; Muhammad Rapi; Zulkarnaim Zulkarnaim (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
The purpose of this study is to produce a valid, practical and effective module that can facilitate students to integrate the biological learning material with related verses in Al Quran. This was a development research (R&D) which referred to 4 D development model with four stages, namely; define, design, develop, and disseminate. The research instruments used were validation sheets, student response questionnaires and learning outcomes tests in the form of 20 multiple choice questions. The data analysis technique used was validity data analysis, practicality data analysis, and effective data analysis. Based on the results of the assessment of validator, the module was met with valid category with an average validity of 3.48. This indicates that the module can be applied in learning. Practical level of the module was in positive category with average practicality was 3.65. This indicates that the module can be used by the students easily. The effectiveness of the module was very effective with a percentage of completeness was 100%.